The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/1751-7915.13644
|View full text |Cite
|
Sign up to set email alerts
|

Oil field microorganisms cause highly localized corrosion on chemically inhibited carbon steel

Abstract: Carbon steel pipelines, a means for crude oil transportation, occasionally experience highly localized perforation caused by microorganisms. While microorganisms grown in laboratory culture tend to corrode steel specimens unevenly, they rarely inflict a corrosion morphology consistent with that of pipelines, where centimetre-sized corrosion features are randomly distributed within vast stretches of otherwise pristine metal surface. In this study, we observed that corrosion inhibitors (CIs), widely used for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 52 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…The effectiveness of these mechanisms, however, depends on the specific system’s conditions and the microorganisms involved. In some cases, they may even become ineffective (Dariva and Galio 2014 , Mand and Enning 2021 ) or act as a source of nutrients for bacterial growth (Edwards and McNeill 2002 , Fang et al 2009 ) Therefore, it is crucial to fill the knowledge gap regarding the mechanisms of action of corrosion inhibitors and bioactive agents, as well as their effects on the development and resistance of biofilms (Bridier et al 2011 , Bas et al 2017 , Kimbell et al 2020 , Tuck et al 2022 ). Despite progress over recent years, knowledge is still scarce and fragmented (Araújo et al 2014 , Huang et al 2020 , Silva et al 2021 , Lima et al 2022 ).…”
Section: Corrosion Managementmentioning
confidence: 99%
“…The effectiveness of these mechanisms, however, depends on the specific system’s conditions and the microorganisms involved. In some cases, they may even become ineffective (Dariva and Galio 2014 , Mand and Enning 2021 ) or act as a source of nutrients for bacterial growth (Edwards and McNeill 2002 , Fang et al 2009 ) Therefore, it is crucial to fill the knowledge gap regarding the mechanisms of action of corrosion inhibitors and bioactive agents, as well as their effects on the development and resistance of biofilms (Bridier et al 2011 , Bas et al 2017 , Kimbell et al 2020 , Tuck et al 2022 ). Despite progress over recent years, knowledge is still scarce and fragmented (Araújo et al 2014 , Huang et al 2020 , Silva et al 2021 , Lima et al 2022 ).…”
Section: Corrosion Managementmentioning
confidence: 99%
“…Quorum sensing is the ability for cell-to-cell communication for gene regulation, and is an important capability governing the establishment of multi-cellular associations such as biofilms [90]. In the context of oil and gas operations, quorum sensing and biofilm formation have both been reported as prerequisites to microbially influenced corrosion [91].…”
Section: Quorum Sensing and Biofilm Formationmentioning
confidence: 99%
“…Moreover, several studies have demonstrated that many factors significantly affect steel corrosion in saline soils. These factors include soil moisture content [ 11 ], pH [ 12 , 13 , 14 ], ion concentration [ 15 , 16 , 17 ], and the presence of microorganisms [ 18 , 19 , 20 , 21 , 22 , 23 ]. Han et al found that corrosion rates increased as the pH of contaminated silty soil decreased [ 24 ].…”
Section: Introductionmentioning
confidence: 99%